2012
DOI: 10.5588/ijtld.11.0655
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of integrated registers for tuberculosis and HIV surveillance in children, Ethiopia, 2007–2009 [Notes from the field]

Abstract: In 2008, Ethiopia implemented tuberculosis (TB) treatment registers that included columns for recording human immunodeficiency virus (HIV) test results (integrated registers) to replace the previous system of separate TB and HIV registers (pre-integration registers). We compared the proportion of children with documented HIV rapid test results at eight hospitals before and after adopting the integrated registers. HIV status was more consistently documented in the integrated registers; however, HIV status for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The high prevalence in TB clinics in our study (7.9%) is consistent with studies from high-prevalence countries (6%–56%) 3,5 but is lower than a previous study from Ethiopia (12%). 4 Although one study in Zimbabwe (a high-prevalence country) found yields up to 18% among OVC <5 years, 11 OVC does not appear high yield in Ethiopia (yield, 0.3%). Some studies from high-prevalence countries focused on children <5 years, 2,11 while our population included children up to 14 years, which may have contributed to the differences in the OVC and malnutrition entry points.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The high prevalence in TB clinics in our study (7.9%) is consistent with studies from high-prevalence countries (6%–56%) 3,5 but is lower than a previous study from Ethiopia (12%). 4 Although one study in Zimbabwe (a high-prevalence country) found yields up to 18% among OVC <5 years, 11 OVC does not appear high yield in Ethiopia (yield, 0.3%). Some studies from high-prevalence countries focused on children <5 years, 2,11 while our population included children up to 14 years, which may have contributed to the differences in the OVC and malnutrition entry points.…”
Section: Discussionmentioning
confidence: 97%
“…Minimum sample size was determined for each of the five entry points by considering client load and number of children tested during the prior fiscal year and assumed pediatric HIV prevalence by entry point from published literature 4 and program data from facilities and implementing partners (Text, Supplemental Digital Content 1, http://links.lww.com/INF/E518, and Table, Supplemental Digital Content 2, http://links.lww.com/INF/E519, respectively). For the OVC entry point, each study facility had an OVC program that referred children for facility-based testing.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation